Monitoring System for Water Turbidity and Air Muda with Microfiltration in IoT-Based Salt Crystallization Process Using Rule-Based Method - Kuswanto, Dwi (Universitas Trunojoyo Madura, 2025)
Salt is a mineral that humans need. Indonesia has abundant biodiversity, including 20,089 hectares of salt-productive land. However, despite this great potential, Indonesia still has to import salt to meet the national needs that continue to increase yearly. The increase in salt consumption is influenced by population growth. Salt is used in two main categories: consumption and industry. An efficient salt production process will produce higher-quality salt. However, currently, many salt farmers are still using manual methods that are less efficient and time-consuming, and also the water used as raw material has not been filtered. Microfiltration is carried out to reduce water turbidity, which aims to filter microscopic objects so that the water used in the salt crystallization process becomes cleaner. Salt production is carried out by the stage of the microfiltration process automatically based on the level of water turbidity, and the height of the salt evaporation container is regulated by the rule-based method as a control on the servo. By conducting this study, the percentage of ultrasonic sensor error reached 22.21%, and the higher the Analog to Digital Converter value was obtained, the lower the turbidity level (NTU). Using the rule-based method allows the condition of the servo motion to be determined with the value obtained through the sensor.